2017
DOI: 10.29356/jmcs.v61i3.345
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Metforminium Succinate by Melting. Crystal Structure, Thermal, Spectroscopic and Dissolution Properties

Abstract: The reaction by melt mixing at 220 °C of the antihyperglycemic drug metformin hydrochloride <strong>1</strong> with dehydrated sodium succinate yields efficiently the organic salt [MET]<sub>2</sub>[SUC] <strong>2</strong> (H-MET<sup>+</sup>= metforminium and SUC<sup>2-</sup> = succinate). Solid state CPMAS NMR <sup>13</sup>C spectroscopy experiments, powder X-ray diffraction and FT-IR results support the formation of the pharmaceutical sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…The chemical shifts assignment in the 15 N-SSNMR experiments presented in Table 1 was made by analogy to the assignments in solution obtained from HMBC and HSQC experiments (Supplementary Figures S2-S4, SM †). In addition, the chemical shifts for the nuclei 1 H, 13 C and 15 N [71,72] in d 6 -DMSO and D 2 O for MET•HCl have been previously reported [73]. In the 15 N-SSNMR spectra for MET•HCl we noted the presence of 4 signals as well as the reported NMR solution [72].…”
Section: Nuclear Magnetic Resonancesupporting
confidence: 73%
“…The chemical shifts assignment in the 15 N-SSNMR experiments presented in Table 1 was made by analogy to the assignments in solution obtained from HMBC and HSQC experiments (Supplementary Figures S2-S4, SM †). In addition, the chemical shifts for the nuclei 1 H, 13 C and 15 N [71,72] in d 6 -DMSO and D 2 O for MET•HCl have been previously reported [73]. In the 15 N-SSNMR spectra for MET•HCl we noted the presence of 4 signals as well as the reported NMR solution [72].…”
Section: Nuclear Magnetic Resonancesupporting
confidence: 73%
“…These results are in agreement with the results of the electron scanning microscope of the same product. The absence of drug melting endothermic peak as a result of its molecular dispersion in the Span 60 matrix did not indicate the role of the matrix in the drug thermal stability (Plata-Vargas et al, 2017). At the same time, a TGA thermogram of all Span 60-encapsulated drugs showed a delayed degradation effect compared to the pure drug ( Figures 3A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…This endothermic transition stage is attributed to the melting of the pure metformin HCl (Bretnall and Clarke, 1998). A huge endothermic peak is also observed directly following the melting of the pure metformin HCl, which is due to the decomposition of the pure drug (Plata-Vargas et al, 2017). More details about the thermal degradation of metformin HCl were reported by Ramachandran et al (Ramukutty et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…32 A huge endothermic peak is also observed directly following the melting of the pure metformin HCl, which is due to the decomposition of the pure drug. 44 More details about the thermal degradation of metformin HCl were also reported. 45 Comparing the DSC scan of the drug in the prepared granules with that of pure drug, it can be concluded that there is no change in the drug crystallinity from the pure form as a result of the granulation process.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%